Effects of intravenous immunoglobulin on the negatively transformed subpopulations of neutrophilic granulocytes in newborns with congenital pneumonia and neonatal sepsis - I. V. Nesterova; S. V. Kovaleva; G. A. Chudilova; L. V. Lomtatidze; T. V. Smerchinskaya; V. N. Chapurina (Медицинская иммунология)
Today, the diagnosis and treatment of severe infectious and inflammatory diseases in newborns, e.g., congenital pneumonia (CP) and neonatal sepsis (NS), present difficult problems. Searching sensitive and specific severity markers of bacterial inflammatory process as well as early and effective treatment are crucial for the outcome and prognosis of these life-threatening diseases. The aim of our study was to assess the effects of intravenous immunoglobulin (IVIG) injections on the negatively transformed subpopulations of neutrophilic granulocytes (NG) СD64-CD16+СD32+СD11b+, СD64+CD16+СD32+СD11b+ and evaluation of their functional activity in newborns with CP and NS. We have observed 38 full-term newborn patients. Group 1 included 19 infants with CP, including 11 children who received conventional therapy and IVIG (group 1.1), and 8 children treated at conventional protocols (group 1.2). Group 2 included 19 children with NS, including 12 children who underwent conventional therapy and IVIG treatment (group 2.1), and 7 children who were subject to conventional therapy (group 2.2). The comparison group consisted of 22 healthy full-term newborns. Testing of NG population included the following parameters: counting the numbers of NG subpopulations which simultaneously expressed CD11b CD64, CD32, CD16, as well as their phenotypic patterns, with regard of the receptor expression density (MFI) using flow cytometric techniques. Moreover, we determined phagocytic and microbicidal activity of the granulocytes. We have revealed negative transformation of СD64-CD16+СD32+СD11b+ and СD64+CD16+СD32+СD11b+ subpopulations of neutrophilic granulocytes in newborns with CP and NS, The diagnostic significance of increased СD64+CD16+СD32+СD11b+NG subpopulation was more pronounced with increasing severity of bacterial infection and inflammatory process, i.e., 18.7-fold in CP, 52.3-fold in NS, along with predominant decrease in expression of appropriate membrane receptors. These phenotypic changes were associated with impaired phagocytic and killing activity of NG. The effect of IVIG on the impaired mechanisms of antibacterial immunity is associated not only with alleviation of IgG deficiency, but also with positive remodeling of negatively transformed subpopulations of СD64-CD16+СD32+СD11b+NG and СD64+CD16+СD32+СD11b+NG, improved effector functions of NG, especially in cases of CP. Thus, following IVIG treatment, a reduced number of СD64-CD16+СD32+СD11b+NG subpopulations was fully recovered in CP, while it increased 1.5 times in NS, and the content of diagnostically significant СD64+CD16+СD32+СD11b+NG subpopulation showed a significantly decrease, both in CP (2-fold) and in NS (2.6-fold). However, this index remained higher than the content of this subpopulation in healthy newborns. At the same time, we have noted the restorative or modulatory effects by changing density of trigger molecules in NG subpopulations. Limitation of the negative NG transformation in their functionally significant subpopulations in newborns with CAP and NS was accompanied by positive clinical effects, i.e., optimization of antibiotic therapy, reduced duration of treatment, and improved mortality rates.